Fall armyworm (Spodoptera frugiperda) management using pheromone-based mass trapping data on summer maize at the PHI platform in Qob Elisa, Lebanon - Kumari, Safaa; Choueiri, Elia; Moukahel, Abdulrahman; Kemal, Seid Ahmed (International Center for Agricultural Research in the Dry Areas, 2024)
The invasive pest, fall armyworm (FAW), Spodoptera frugiperda, poses a significant threat to irrigated summer maize production in Lebanon and other countries in West Asia and North Africa, endangering food security and income to farmers. A field study conducted at Qob Elias (PHI-IP site), Bekaa valley in Lebanon during the summer of 2024 to evaluate the effectiveness of insecticides based on pheromone trap to manage FAW affecting summer maize. Three maize fields were planted with imported cultivars and FAW- was monitored using specific pheromone traps to track pest dynamics. Foliar insecticides were applied based on trap data to ensure timely interventions. Results revealed that FAW population was at peak between September 10 and 29, underscoring the importance of early planting and pre-peak management. The IPM approach significantly reduced FAW damage, achieving unobservable infestation levels compared to neighboring farmers employing traditional methods. This study highlights the critical role of pheromone traps in monitoring pest populations and reducing insecticide use, offering an effective and sustainable strategy for managing FAW in Lebanese maize fields. Neighboring farmers were engaged in knowledge-sharing activities, fostering broader adoption of these IPM practices in collaboration with ICARDA and LARI scientists.